Description some Pistacia phenotypes Spread in some villages of Lattakia district. - مخول, جرجس; قرحيلي, حلا (Latakia University Journal -Biological Sciences Series, 2022)
This research was conducted during the period of 2019 – 2020 in two areas in Lattakia district varied in height above sea level (20 and 200 m) in order to survey and evaluate some pistacia phenotypes. 17 samples were determined and each sample was considered a phenotype for the description of morphological and phenological characterization and for the determination of the degree of morphological relationship between those types in addition to setting their own taxonomic keys. Morphological analysis was done based on 13 morphology characteristics (leaves, catkins, fruits) in addition to a cluster analysis for all types. The morphological tree for all types showed two main groups with a contrast ratio of (94%), the first group included 10 types from two locations with a contrast ratio (79%), and the second group included 7 types with a contrast ratio (83%). The degree of morphological similary is variable between the studied types.